2018
DOI: 10.1242/jeb.180166
|View full text |Cite
|
Sign up to set email alerts
|

Low thermal dependence of the contractile properties of a wing muscle in the batCarollia perspicillata

Abstract: Temperature affects contractile rate properties in muscle, which may affect locomotor performance. Endotherms are known to maintain high core body temperatures, but temperatures in the periphery of the body can fluctuate. Such a phenomenon occurs in bats, whose wing musculature is relatively poorly insulated, resulting in substantially depressed temperatures in the distal wing. We examined a wing muscle in the small-bodied tropical bat and a hindlimb muscle in the laboratory mouse at 5°C intervals from 22 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Among the possible mechanisms are altered flight mechanics, changes in muscle recruitment, and changes in the thermal dependence of contractile properties. In regard to the latter possibility, a forearm extensor muscle in C. perspicillata has lower thermal dependence than expected based on data from other mammalian skeletal muscles, consistent with a functional adaptation to habitually low temperatures in this muscle [3]. We suggest that a thermoregulatory trade-off exists between the performance benefits of keeping distal muscles warm and the energetic benefit of conserving energy by allowing distal regions to cool.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Among the possible mechanisms are altered flight mechanics, changes in muscle recruitment, and changes in the thermal dependence of contractile properties. In regard to the latter possibility, a forearm extensor muscle in C. perspicillata has lower thermal dependence than expected based on data from other mammalian skeletal muscles, consistent with a functional adaptation to habitually low temperatures in this muscle [3]. We suggest that a thermoregulatory trade-off exists between the performance benefits of keeping distal muscles warm and the energetic benefit of conserving energy by allowing distal regions to cool.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, variable limb muscle temperatures may have performance costs for locomoting animals, and/or put selective pressure on the temperature sensitivity of physiochemical processes within limbs. We previously reported that an extensor muscle in the forearm of the bat Carollia perspicillata has a lower than expected thermal sensitivity of contractile rates, and have hypothesized that this is an adaptation to routine operation below core body temperature [3].…”
Section: Introductionmentioning
confidence: 95%
“…From this curve, we recorded the peak contractile velocity (i.e. the peak contractile speed under no load; V max ) as the x-intercept of the fitted force-velocity relationship, as well as the contractile velocity at 40% of P 0 (V 40 ; Rummel et al, 2018).…”
Section: Curve Fittingmentioning
confidence: 99%
“…Work loop power output showed higher thermal sensitivity in muscle isolated from the deep endothermic core of yellow fin tuna, Thunnus albacares , than from the more superficial region of skeletal muscle in this fish (Altringham and Block, 1997). A comparison between bat, Carollia perspicillata , wing muscle (extensor carpi radialis longus) and mouse, M. musculus , limb muscle (extensor digitorum longus) demonstrated that isometric force generation and relaxation times and maximal shortening velocity had lower thermal sensitivity, below core body temperature, in the bat wing muscle, which is likely to be subjected to much higher temperature ranges during flight than would occur in mouse limb muscle (Rummel et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%